laminate
Patent Information
- Application Number
- JP2023131511
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-21
AI Technical Summary
【0006】 本開示によれば、離型性に優れるとともに、基材層に対する密着性にも優れる4-メチル-1-ペンテン系重合体層を含む積層体を提供できる。
Smart Images

Figure 2025026127000005 
Figure 2025026127000006 
Figure 2025026127000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a laminate. [Background technology]
[0002] 4-methyl-1-pentene polymers have excellent releasability due to their low surface tension and also have high heat resistance, and therefore laminates including a 4-methyl-1-pentene polymer layer and a substrate layer are used as industrial release films and the like (see, for example, Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-74775 A [Patent Document 2] JP 2013-227421 A [Patent Document 3] JP 2015-34258 A Summary of the Invention [Problem to be solved by the invention]
[0004] Although the 4-methyl-1-pentene polymer layer has excellent releasability, it tends to have low adhesion to the base layer. One object of the present disclosure is to provide a laminate including a 4-methyl-1-pentene polymer layer that has excellent releasability and excellent adhesion to the base layer. [Means for solving the problem]
[0005] The present disclosure relates to, for example, the following [1] to
[12] . [1] A laminate comprising a substrate layer (I) and a layer (II) formed of a composition (X) containing a graft-modified 4-methyl-1-pentene polymer (B) and an isocyanate compound (C) that satisfy the following requirements (a) to (c): (a) a melting point (Tm) measured by differential scanning calorimetry (DSC) of greater than 180°C and less than or equal to 220°C; (b) The endothermic end temperature (TmE) in the melting (endothermic) curve measured by differential scanning calorimetry (DSC) is 230°C or lower; (c) The heat generation onset temperature (TcS) in the crystallization (heat generation) curve measured by differential scanning calorimetry (DSC) is 210°C or lower. [2] The laminate according to item [1], wherein the graft-modified 4-methyl-1-pentene polymer (B) has an intrinsic viscosity [η] of 0.5 to 5.0 dl / g as measured in decalin at 135° C. [3] The graft-modified 4-methyl-1-pentene polymer (B) is a graft-modified product of the 4-methyl-1-pentene polymer (A), The 4-methyl-1-pentene polymer (A) contains a structural unit (U1) derived from 4-methyl-1-pentene, and, if desired, a structural unit (U2) derived from an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene), The laminate according to item [1] or [2], wherein the 4-methyl-1-pentene polymer (A) has a content of the structural unit (U1) of 84 to 100 mol % and a content of the structural unit (U2) of 0 to 16 mol % (wherein the sum of the content of the structural unit (U1) and the content of the structural unit (U2) is 100 mol %). [4] The laminate according to any one of items [1] to [3], wherein the base layer (I) contains a polyolefin having a melting point (Tm) of 200° C. or lower as measured by a differential scanning calorimeter (DSC). [5] The laminate according to any one of items [1] to [4], wherein the graft-modified amount of the graft-modified 4-methyl-1-pentene polymer (B) is 0.1 to 5.0% by mass. [6] The laminate according to any one of items [1] to [5], wherein the content of the isocyanate compound (C) in the composition (X) is 0.2 to 30 parts by mass per 100 parts by mass of the graft-modified 4-methyl-1-pentene polymer (B). [7] The laminate according to any one of items [1] to [6], wherein the surface free energy of the layer (II) on the side opposite to the side facing the base layer (I) is 32 mN / m or less. [8] The laminate according to any one of items [1] to [7], wherein the layer (II) has a water contact angle of 97° or more on a surface opposite to the surface facing the base layer (I). [9] The laminate according to any one of items [3] to [8], wherein the structural unit (U2) of the 4-methyl-1-pentene polymer (A) is a structural unit derived from an α-olefin having 6 to 18 carbon atoms (excluding 4-methyl-1-pentene).
[10] The laminate according to any one of items [1] to [9], wherein the layer (II) has a thickness of 25 μm or less.
[11] The laminate according to any one of items [4] to
[11] , wherein the polyolefin in the base layer (I) having a melting point (Tm) of 200° C. or less includes at least one selected from the group consisting of polypropylene and polyethylene.
[12] The laminate according to item
[11] , wherein the polyolefin in the base layer (I) having a melting point (Tm) of 200 ° C. or less includes polypropylene. Effect of the Invention
[0006] According to the present disclosure, it is possible to provide a laminate including a 4-methyl-1-pentene polymer layer that has excellent releasability and adhesion to a base layer. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a cross-sectional view of a laminate according to one embodiment. [Diagram 2] FIG. 2 is a cross-sectional view of a laminate according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] In this specification, unless otherwise specified, the expression "A to B" regarding a numerical range means that it is equal to or greater than A and equal to or less than B. For example, the expression "10 to 20%" means equal to or greater than 10% and equal to or less than 20%. Additionally, the various monomers in the present disclosure may be derived from fossil raw materials or biomass.
[0009] The laminate of the present disclosure will be described in detail below. The laminate of the present disclosure includes a substrate layer (I) and a layer (II) formed from a composition (X) containing a graft-modified 4-methyl-1-pentene polymer (B) and an isocyanate compound (C). The composition (X) will be described below, and then the laminate will be described.
[0010] <Composition (X)> The composition (X) contains a graft-modified 4-methyl-1-pentene polymer (B) and an isocyanate compound (C).
[0011] [Graft modified 4-methyl-1-pentene polymer (B)] The graft-modified 4-methyl-1-pentene polymer (B) (hereinafter also referred to as "polymer (B)") is a graft-modified product of the 4-methyl-1-pentene polymer (A) (hereinafter also referred to as "polymer (A)"), and is obtained, for example, by graft-modifying the polymer (A) with an ethylenically unsaturated monomer.
[0012] Each of the polymers (A) and (B) contains a structural unit derived from 4-methyl-1-pentene. Each of the polymers (A) and (B) may further contain a structural unit derived from an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene).
[0013] In the following description, the structural unit derived from 4-methyl-1-pentene in polymer (A) and polymer (B) is also referred to as "structural unit (U1)". Similarly, the structural unit derived from an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) in polymer (A) and polymer (B) is also referred to as "structural unit (U2)".
[0014] The polymer (B) satisfies the requirements (a) to (c) described below.
[0015] [Requirement (a)] The melting point (Tm) of the polymer (B) is more than 180°C and not more than 220°C, preferably 184 to 217°C, and more preferably 188 to 215°C. The melting point (Tm) is measured by a differential scanning calorimeter (DSC), and the details of the measurement method are described in the Examples section. The polymer (B) having a melting point (Tm) in the above range has excellent heat resistance. Therefore, the layer (II) formed from the composition (X) also tends to have excellent heat resistance.
[0016] The melting point (Tm) tends to depend on the stereoregularity of the polymer (B) and the content of the structural unit (U2) in the polymer (B). Therefore, the melting point (Tm) can be adjusted by using an olefin polymerization catalyst described later and further controlling the content of the structural unit (U2).
[0017] [Requirement (b)] The endothermic end temperature (TmE) in the melting (endothermic) curve of the polymer (B) is 230°C or less, preferably less than 230°C, more preferably less than 228°C, and even more preferably less than 228°C. The endothermic end temperature is measured by DSC, and the details of the measurement method are described in the Examples section. The endothermic end temperature means the temperature at which melting is completed. The endothermic end temperature and the heat generation start temperature described later are indexes different from the onset and offset, which are generally the intersection points between the baseline and the tangent to the steady line.
[0018] The endothermic end temperature can be adjusted to a desired value, for example, by appropriately selecting an olefin polymerization catalyst when synthesizing the polymer (A) and by controlling the content of the structural unit (U2).
[0019] The polymer (B) having an endothermic end temperature within the above range has excellent heat resistance. Therefore, the layer (II) formed from the composition (X) also tends to have excellent heat resistance. The polymer (B) having an endothermic end temperature within the above range is more easily dissolved in a solvent that can be used when preparing a coating agent than a graft-modified 4-methyl-1-pentene polymer having an endothermic end temperature outside the above range. Therefore, the properties of a coating agent prepared using the polymer (B) having an endothermic end temperature within the above range tend to be uniform.
[0020] [Requirement (c)] The exothermic onset temperature (TcS) in the crystallization (exothermic) curve of the polymer (B) is 210° C. or lower, preferably lower than 210° C., more preferably lower than 200° C., and even more preferably lower than 200° C. The exothermic onset temperature is measured by DSC, and the details of the measurement method are described in the Examples section.
[0021] The exotherm initiation temperature can be adjusted to a desired value, for example, by appropriately selecting an olefin polymerization catalyst when synthesizing the polymer (A) and by controlling the content of the structural unit (U2).
[0022] The polymer (B) having a heat generation onset temperature within the above range has excellent heat resistance. Therefore, the layer (II) formed from the composition (X) also tends to have excellent heat resistance. The polymer (B) having a heat generation onset temperature within the above range is more easily dissolved in a solvent that can be used when preparing a coating agent than a graft-modified 4-methyl-1-pentene polymer having a heat generation onset temperature outside the above range. Therefore, the properties of a coating agent prepared using the polymer (B) having a heat generation onset temperature within the above range tend to be uniform.
[0023] Since the polymer (B) satisfies the requirements (a) to (c), it has excellent solubility in a solvent while maintaining heat resistance. In addition, since the polymer (B) that satisfies the requirements (a) to (c) has excellent solubility in a solvent, it is easy to maintain a dissolved state in the solvent. Therefore, the polymer (B) that satisfies the requirements (a) to (c) has good storage stability when dissolved in a solvent, compared with a graft-modified 4-methyl-1-pentene polymer that does not satisfy one or more of the requirements (a) to (c).
[0024] The crystallization temperature (Tc) of the polymer (B) is preferably 110 to 200° C., more preferably 120 to 195° C., and further preferably 130 to 190° C. The crystallization temperature is measured by DSC, and the details of the measurement method are described in the Examples section. The polymer (B) having a crystallization temperature in the above range is preferred from the viewpoints of heat resistance and moldability.
[0025] The crystallization temperature (Tc) tends to depend on the stereoregularity of the polymer (B) and the content of the structural unit (U2) in the polymer (B). Therefore, the crystallization temperature (Tc) can be adjusted by using an olefin polymerization catalyst described later and further controlling the content of the structural unit (U2).
[0026] The intrinsic viscosity [η] of the polymer (B) measured in decalin at 135°C is preferably 0.5 to 5.0 dl / g, more preferably 0.6 to 4.0 dl / g, and even more preferably 0.8 to 3.0 dl / g. The polymer (B) having an intrinsic viscosity [η] within the above range has good heat resistance. The coating agent containing the polymer (B) having an intrinsic viscosity [η] within the above range has excellent coatability and is suitable for forming the layer (II). The intrinsic viscosity [η] can be adjusted, for example, by the amount of hydrogen added in the polymerization step when producing the polymer (A).
[0027] In the polymer (A), the content of the structural unit (U1) is preferably 84 to 100 mol%, more preferably 87 to 99.0 mol%, and even more preferably 90 to 98.5 mol%, and the content of the structural unit (U2) is preferably 0 to 16 mol%, more preferably 1.0 to 13 mol%, and even more preferably 1.5 to 10 mol%, where the sum of the content of the structural unit (U1) and the content of the structural unit (U2) is taken as 100 mol%.
[0028] The content of each of the structural units (U1) and (U2) is 13 It is measured by C-NMR, specifically, measured by the method described in the Examples section. The polymer (A) whose content of structural unit (U1) and content of structural unit (U2) are within the above ranges tends to have excellent heat resistance, and therefore the polymer (B) also tends to have excellent heat resistance. Therefore, the layer (II) formed from the composition (X) also tends to have excellent heat resistance.
[0029] The α-olefin from which the structural unit (U2) is derived is an α-olefin having 2 to 20 carbon atoms, preferably an α-olefin having 6 to 18 carbon atoms. The α-olefin from which the structural unit (U2) is derived is preferably a linear α-olefin. Examples of the α-olefin from which the structural unit (U2) is derived include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene, and 1-eicosene. Among these, linear α-olefins having 6 to 18 carbon atoms are preferred from the viewpoint of heat resistance. Specifically, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-heptadecene and 1-octadecene are preferred, and among these, 1-decene, 1-hexadecene and 1-octadecene are particularly preferred.
[0030] The structural unit (U2) in the polymer (A) may be of one type, or of two or more types. The structural unit (U2) in the polymer (B) may be of one type, or of two or more types.
[0031] The polymer (A) may be a copolymer in which the structural units derived from the polymerizable monomer are only the structural units (U1) and (U2). In this case, the total content of the structural units (U1) and (U2) is 100 mol % of all the structural units derived from the polymerizable monomers in the polymer (A).
[0032] In addition to the structural units (U1) and (U2), the polymer (A) may further contain structural units derived from other polymerizable monomers other than 4-methyl-1-pentene and α-olefins having 2 to 20 carbon atoms. In the polymer (A), the content of all structural units derived from other polymerizable monomers in 100 mol % of all structural units derived from polymerizable monomers is preferably 10 mol % or less, more preferably 5 mol % or less, and even more preferably 3 mol % or less.
[0033] The constituent units derived from other polymerizable monomers in the polymer (A) may be of one type or two or more types. The constituent units derived from other polymerizable monomers in the polymer (B) may be of one type or two or more types.
[0034] Specific preferred examples of other polymerizable monomers include vinyl compounds having a cyclic structure, such as styrene, vinylcyclopentane, vinylcyclohexane, and vinylnorbornane; vinyl esters, such as vinyl acetate; unsaturated organic acids or derivatives thereof, such as maleic anhydride; conjugated dienes, such as butadiene, isoprene, pentadiene, and 2,3-dimethylbutadiene; 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, 7-methyl-1,6-octadiene, and the like. non-conjugated polyenes such as dicyclopentadiene, cyclohexadiene, dicyclooctadiene, methylenenorbornene, 5-vinyl-2-norbornene, 5-ethylidene-2-norbornene, 5-methylene-2-norbornene, 5-isopropylidene-2-norbornene, 6-chloromethyl-5-isopropenyl-2-norbornene, 2,3-diisopropylidene-5-norbornene, 2-ethylidene-3-isopropylidene-5-norbornene, and 2-propenyl-2,2-norbornadiene.
[0035] The polymer (A) can be obtained, for example, by polymerizing 4-methyl-1-pentene, optionally together with an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) and, optionally, together with the other polymerizable monomers described above, in the presence of an olefin polymerization catalyst by a known method.
[0036] Examples of olefin polymerization catalysts that can be used in the production of polymer (A) include metallocene catalysts.Preferred metallocene catalysts include those described in WO 01 / 053369, WO 01 / 027124, JP-A 03-193796, JP-A 02-041303, WO 06 / 025540, or WO 2014 / 123212.
[0037] The graft-modified 4-methyl-1-pentene polymer (B) can be obtained, for example, by graft-modifying the 4-methyl-1-pentene polymer (A) with an ethylenically unsaturated monomer.
[0038] The amount of graft modification of the polymer (B) is preferably 0.1 to 5.0% by mass, more preferably 0.3 to 4.0% by mass, and further preferably 0.5 to 3.0% by mass. The amount of graft modification means the ratio of the mass of the structural unit derived from the ethylenically unsaturated monomer used in the graft modification to the mass of the polymer (B). The amount of graft modification is measured by infrared spectroscopy (IR), and an example of the measurement conditions is described in the Examples section. The layer (II) formed from the composition (X) containing the polymer (B) and the isocyanate compound (C) having the amount of graft modification in the above range tends to have an excellent balance between releasability and adhesion to the base layer (I).
[0039] The ethylenically unsaturated monomer is preferably an ethylenically unsaturated monomer having a functional group capable of reacting with the isocyanate group contained in the isocyanate compound (C), and more preferably an unsaturated carboxylic acid or a derivative of an unsaturated carboxylic acid. Examples of the unsaturated carboxylic acid and its derivative include an unsaturated compound having one or more carboxylic acid groups, an ester of an unsaturated compound having one or more carboxylic acid groups and an alkyl alcohol, and an unsaturated compound having one or more carboxylic acid anhydride groups.
[0040] Examples of the unsaturated group contained in the unsaturated compound include a vinyl group, a vinylene group, and an unsaturated cyclic hydrocarbon group. Among the ethylenically unsaturated monomers, an unsaturated dicarboxylic acid or an acid anhydride thereof is preferable, and maleic acid, nadic acid, or an acid anhydride thereof is more preferable.
[0041] The ethylenically unsaturated monomer may be used alone or in combination with two or more other types. That is, the structural unit derived from the ethylenically unsaturated monomer used in the graft modification in the polymer (B) may be either alone or in combination with two or more other types.
[0042] Examples of the method for grafting the 4-methyl-1-pentene polymer (A) with an ethylenically unsaturated monomer include conventionally known graft polymerization methods such as a solution method and a melt kneading method. Examples of the graft polymerization method include a method in which the 4-methyl-1-pentene polymer (A) is melted, an ethylenically unsaturated monomer is added, and a method in which the 4-methyl-1-pentene polymer (A) is dissolved in a solvent to form a solution, and an ethylenically unsaturated monomer is added thereto to cause a graft reaction.
[0043] The content of the polymer (B) in 100% by mass of the solid content of the composition (X) is preferably more than 50% by mass, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more. The content of the polymer (B) in 100% by mass of the solid content of the composition (X) may be, for example, less than 100% by mass, 99.9% by mass or less, 99% by mass or less, 98% by mass or less, 95% by mass or less, or 90% by mass or less. In this specification, the solid content of the composition (X) refers to all components except the solvent (D) described later.
[0044] [Isocyanate compound (C)] The composition (X) contains an isocyanate compound (C).
[0045] The isocyanate compound (C) is not particularly limited as long as it is a compound having an isocyanate group, but from the viewpoint of improving curability, it is preferably a polyfunctional isocyanate compound having two or more isocyanate groups in one molecule.
[0046] Examples of bifunctional isocyanate compounds having two isocyanate groups in one molecule include aliphatic diisocyanates such as methylene diisocyanate, dimethylene diisocyanate, trimethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, dipropyl ether diisocyanate, 2,2-dimethylpentane diisocyanate, 3-methoxyhexane diisocyanate, octamethylene diisocyanate, 2,2,4-trimethylpentane diisocyanate, nonamethylene diisocyanate, decamethylene diisocyanate, 3-butoxyhexane diisocyanate, 1,4-butylene glycol dipropyl ether diisocyanate, and thiodihexyl diisocyanate; Aromatic diisocyanates such as m-phenylene diisocyanate, p-phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, dimethylbenzene diisocyanate, ethylbenzene diisocyanate, isopropylbenzene diisocyanate, tolidine diisocyanate, 1,4-naphthalene diisocyanate, 1,5-naphthalene diisocyanate, 2,6-naphthalene diisocyanate, 2,7-naphthalene diisocyanate, metaxylylene diisocyanate, paraxylylene diisocyanate, and tetramethylxylylene diisocyanate; and Examples of such diisocyanates include alicyclic diisocyanates such as hydrogenated xylylene diisocyanate, isophorone diisocyanate, and dicyclohexylmethane 4,4'-diisocyanate.
[0047] The isocyanate compound (C) may be a biuret or isocyanurate, which is a trimer of a difunctional isocyanate compound, an adduct between a polyol such as trimethylolpropane and a difunctional isocyanate compound (i.e., an adduct), or an adduct between an alcohol such as methanol and a difunctional isocyanate compound (i.e., an allophanate).
[0048] Among these, from the viewpoint of suppressing discoloration of the laminate, the isocyanate compound (C) is preferably an aliphatic isocyanate compound, more preferably an aliphatic isocyanate compound having two or more isocyanate groups in one molecule, further preferably an aliphatic diisocyanate, an isocyanurate of an aliphatic diisocyanate, an allophanate of an aliphatic diisocyanate and an alcohol, or an adduct of an aliphatic diisocyanate and a polyol, and particularly preferably an aliphatic diisocyanate or an isocyanurate of an aliphatic diisocyanate.
[0049] The isocyanate compound (C) in the composition (X) may be one type or two or more types.
[0050] The content of the isocyanate compound (C) in the composition (X) is preferably 0.2 to 30 parts by mass, more preferably 0.3 to 25 parts by mass, and even more preferably 0.4 to 20 parts by mass, based on 100 parts by mass of the polymer (B). The composition (X) having the content of the isocyanate compound (C) within the above range tends to have excellent storage stability and tends to be able to easily form a layer (II) having excellent adhesion to the base layer (I). The content of the isocyanate compound (C) in the composition (X) may be 10 parts by mass or less based on 100 parts by mass of the polymer (B). Such a composition (X) tends to have better storage stability.
[0051] [Solvent (D)] The composition (X) may contain a solvent (D). The composition (X) containing the solvent (D) may be, for example, liquid and may be a coating agent. In one embodiment, the composition (X) may be a coating agent in which the polymer (B) is dissolved or dispersed in the solvent (D).
[0052] The solvent (D) is not particularly limited as long as it can dissolve or disperse the polymer (B), but is preferably an organic solvent. Examples of the organic solvent include aliphatic hydrocarbons such as n-hexane, n-heptane, n-octane, cyclohexane, methylcyclohexane, ethylcyclohexane, and ethyl acetate; and aromatic hydrocarbons such as toluene and xylene. Among these, toluene, cyclohexane, methylcyclohexane, and ethyl acetate can be preferably used. The solvent (D) is, for example, a solvent that is liquid at room temperature (25°C) and has a boiling point of 150°C or less at 1 atmospheric pressure.
[0053] The composition (X) may contain one or more solvents (D).
[0054] When the composition (X) contains the solvent (D), the content of the solvent (D) is preferably 50 to 99.9% by mass, more preferably 70 to 99% by mass, and further preferably 90 to 98% by mass. Such a composition (X) is suitable, for example, as a coating agent. When the content of the solvent (D) contained in the composition (X) is within the above range, the composition (X) can be easily applied to the substrate layer (I) described below.
[0055] When composition (X) contains solvent (D), the solid content of composition (X) is preferably 0.1 to 50 mass%, more preferably 1 to 30 mass%, and further preferably 2 to 10 mass%. When the solid content of composition (X) is within the above range, a good balance is achieved between the handleability of composition (X) and the ease of removing solvent (D) from composition (X) when forming layer (II).
[0056] [Other ingredients] Composition (X) may further contain other components as necessary. Examples of other components include antioxidants, heat stabilizers, weather stabilizers, antistatic agents, slip agents, leveling agents, reinforcing agents, antiblocking agents, antifogging agents, lubricants, dyes, pigments, natural oils, synthetic oils, waxes, and fillers. The layer (II) formed from composition (X) may also contain the above-mentioned other components.
[0057] The total content of other components in composition (X) is not particularly limited, but is preferably 0.005 to 5 mass %, more preferably 0.01 to 3 mass %, based on 100 mass % of the solid content of composition (X).
[0058] [Method for producing composition (X)] The composition (X) can be produced, for example, by mixing the polymer (B), the isocyanate compound (C), and optionally the solvent (D), and optionally other components. The coating agent, which is one embodiment of the composition (X), can be produced, for example, by adding the polymer (B), the isocyanate compound (C), and optionally other components to the solvent (D), and stirring the mixture for a predetermined period of time at a temperature below the boiling point of the solvent (D).
[0059] <Laminate> The laminate of the present disclosure includes a substrate layer (I) and a layer (II) formed from the above-described composition (X).
[0060] The layer (II) contained in the laminate may be one layer or two or more layers. When the laminate contains two or more layers (II), the two or more layers (II) may be the same or different from each other.
[0061] The laminate may include a layer (II) on only one side of the substrate layer (I), or may include layers (II) on both sides of the substrate layer (I). For example, the laminate may include a substrate layer (I) and a layer (II) provided on one side of the substrate layer (I), or may include a first layer (II), a substrate layer (I), and a second layer (II) in this order in the stacking direction.
[0062] Figures 1 and 2 show cross-sectional views of a laminate according to one embodiment. The laminate 1 shown in Figure 1 includes a base layer (I) 10 and a layer (II) 20. The laminate 1 shown in Figure 2 includes a first layer (II) 20A, a base layer (I) 10, and a second layer (II) 20B.
[0063] The thickness of the laminate of the present disclosure is preferably 10 to 600 μm, more preferably 20 to 500 μm, even more preferably 30 to 400 μm, still more preferably 40 to 300 μm, and particularly preferably 50 to 200 μm. In this specification, the thickness of the laminate and each layer is measured by observing the cross section of the laminate in a direction perpendicular to the surface of the laminate with a scanning electron microscope (SEM).
[0064] [Base material layer (I)] The substrate layer (I) contains, for example, a thermoplastic resin. Examples of the thermoplastic resin include polyolefin, polyester, and polyamide. Examples of the polyolefin include polyethylene, polypropylene, polybutene, and poly-4-methyl-1-pentene. Examples of the polyethylene include high-density polyethylene, medium-density polyethylene, high-pressure low-density polyethylene, and linear low-density polyethylene. Examples of the polyester include polyethylene terephthalate and polyethylene naphthalate. Examples of the polyamide include polyamide 6, polyamide 66, polyamide 12, and polyamide 6-66 copolymer. Among the thermoplastic resins, polyolefin is preferred from the viewpoint of adhesion to the layer (II), polyethylene and polypropylene are more preferred, and polypropylene is even more preferred.
[0065] Examples of polypropylene include propylene homopolymers and propylene copolymers. The propylene copolymer may be, for example, a random copolymer or a block copolymer. Examples of comonomers copolymerized with propylene in the propylene copolymer include α-olefins other than propylene and diene compounds. Examples of α-olefins other than propylene include α-olefins having 2 to 20 carbon atoms (excluding propylene), such as ethylene, 1-butene, 1-pentene, 3-methyl-1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, and 1-tetradecene.
[0066] The content of structural units derived from propylene in the polypropylene is preferably 85 mol % or more, more preferably 90 mol % or more, and the content of structural units derived from the above comonomers is preferably 15 mol % or less, more preferably 10 mol % or less.
[0067] Specific examples of polypropylene include propylene homopolymer, propylene-ethylene random copolymer, propylene-1-butene random copolymer, propylene-1-butene-ethylene random copolymer, propylene-1-hexene random copolymer, propylene-3-methyl-1-butene random copolymer, and propylene-4-methyl-1-pentene random copolymer.
[0068] The melt flow rate (MFR) of polypropylene, measured in accordance with ASTM D 1238 at a temperature of 230°C under a load of 2.16 kg, is preferably 0.1 to 100 g / 10 min, more preferably 0.3 to 30 g / 10 min, further preferably 0.5 to 20 g / 10 min, and particularly preferably 1 to 10 g / 10 min.
[0069] The substrate layer (I) may contain one or more thermoplastic resins.
[0070] The content of the thermoplastic resin (e.g., polyolefin) in the base layer (I) is preferably more than 50% by mass, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more. In one embodiment, the base layer (I) contains polypropylene. In one embodiment, the content of polypropylene in the base layer (I) is preferably more than 50% by mass, more preferably 60% by mass or more, even more preferably 70% by mass or more, still more preferably 80% by mass or more, and particularly preferably 90% by mass or more.
[0071] The melting point (Tm) of the polyolefin is preferably 200° C. or lower, more preferably 190° C. or lower, even more preferably 180° C. or lower, and particularly preferably 175° C. or lower. The melting point (Tm) of the polyolefin is preferably 120° C. or higher, more preferably 130° C. or higher, even more preferably 140° C. or higher, and particularly preferably 150° C. or higher. The melting point (Tm) is measured by a differential scanning calorimeter (DSC), and the details of the measurement method are described in the Examples section. When the melting point (Tm) of the polyolefin is within the above range, it is possible to easily form a film that serves as the substrate, and the film can be used as a general-purpose substrate for packaging materials and the like.
[0072] The substrate layer (I) may contain additives, such as heat stabilizers, weather stabilizers, ultraviolet absorbers, lubricants, slip agents, nucleating agents, antiblocking agents, antistatic agents, antifogging agents, pigments, dyes, and inorganic or organic fillers. The substrate layer (I) may contain one or more additives.
[0073] The substrate layer (I) may be, for example, a substrate film. The substrate film may contain, for example, the above-mentioned thermoplastic resin, and may contain, if desired, the above-mentioned additives. The substrate film may be produced, for example, by an extrusion molding method such as a T-die casting method and an inflation molding method, or a solution casting method. The substrate film may be stretched. The substrate film may be, for example, a uniaxially stretched film or a biaxially stretched film.
[0074] The substrate film may be a single layer or a multilayer.
[0075] The surface of the base layer (I) in contact with the layer (II) may be subjected to a conventionally known surface treatment such as a corona treatment. The surface treatment can improve, for example, the adhesive strength between the base layer (I) and the layer (II).
[0076] The thickness of the substrate layer (I) is preferably 10 to 500 μm, more preferably 20 to 400 μm, even more preferably 30 to 300 μm, still more preferably 40 to 200 μm, and particularly preferably 50 to 150 μm.
[0077] [Layer (II)] The layer (II) is a layer formed from the above-mentioned composition (X). In one embodiment, the layer (II) contains a reaction product of the polymer (B) and the isocyanate compound (C). The layer (II) formed from the composition (X) has excellent adhesion to the substrate layer (I). This is presumably because the polymer (B) and the isocyanate compound (C) chemically and physically interact with each other due to the curing reaction between the polymer (B) and the isocyanate compound (C).
[0078] In one embodiment, the laminate of the present disclosure preferably includes a layer (II) constituting one of the outermost layers, or preferably includes a first layer (II) constituting one of the outermost layers and a second layer (II) constituting the other outermost layer. Such a laminate is preferably used as a release film as described later.
[0079] The surface free energy of the layer (II) on the side opposite to the surface facing the base layer (I) is preferably 32 mN / m or less, more preferably 30 mN / m or less, and even more preferably 28 mN / m or less. The surface free energy of the layer (II) may be, for example, 15 mN / m or more, or 20 mN / m or more. The layer (II) having a surface free energy in the above range tends to have excellent releasability. The surface free energy is measured by the method described in the Examples section.
[0080] The water contact angle of the layer (II) on the surface opposite to the surface facing the base layer (I) is preferably 97° or more, more preferably 98° or more, and even more preferably 99° or more. The water contact angle of the layer (II) may be, for example, 135° or less, or 130° or less. The layer (II) having a water contact angle in the above range tends to have high hydrophobicity and high releasability against highly polar materials, and also tends to have excellent water repellency. The water contact angle is measured by the method described in the Examples section.
[0081] The thickness of the layer (II) is preferably 25 μm or less, more preferably 0.01 to 20 μm, even more preferably 0.03 to 10 μm, even more preferably 0.05 to 5 μm, and particularly preferably 0.1 to 3 μm. When the thickness of the layer (II) is within the above range, even if the layer (II) is formed only on one side of the base layer (I), the obtained laminate is less likely to curl. Furthermore, when the thickness of the layer (II) is within the above range, even if the base layer (I) does not have a multilayer structure provided with an intermediate layer for suppressing curl, the laminate is less likely to curl.
[0082] [Other layers] The laminate of the present disclosure may further include layers other than the above-mentioned substrate layer (I) and layer (II). The laminate may further include a primer layer, for example, between the substrate layer (I) and layer (II). The primer layer is provided, for example, to improve the adhesion between the substrate layer (I) and layer (II). The primer layer is provided, for example, on the surface of the substrate layer (I).
[0083] [Method of manufacturing laminate] The laminate of the present disclosure can be suitably produced, for example, by the following production method: That is, the laminate can be produced by a method including a step (1) of preparing a composition (X) containing a polymer (B), an isocyanate compound (C) and a solvent (D), and a step (2) of applying the composition (X) to at least one surface of a substrate layer (I) to form a layer (II).
[0084] An example of the treatment carried out in step (2) for forming the layer (II) will be described below. In this example, a coating agent, which is one embodiment of the composition (X), is used. Specifically, in step (2), the coating agent is applied to at least one surface of the substrate layer (I) and heated to a temperature close to the boiling point of the solvent (D) in the coating agent to remove the solvent (D) in the coating agent to a certain extent. Examples of methods for applying the coating agent include application using a brush or paintbrush, spraying, screen printing, flow coating, spin coating, and dipping, as well as methods using a bar coater, a T-die, a T-die with a bar, a doctor knife, roll coating, and die coating.
[0085] The removal of the solvent (D) does not only mean the complete removal of the solvent (D) from the coating agent, but also includes the removal of the solvent (D) to such an extent that a layer can be formed. Specifically, the removal of the solvent (D) includes the removal of the solvent (D) until the content of the solvent (D) is about 0.001 to 0.5 mass% relative to 100% by mass of the layer (II) formed using the coating agent. The method for removing the solvent (D) is not particularly limited, and the solvent (D) may be dried by leaving it, but the solvent (D) is generally removed by heating and drying at 30 to 220°C. The heating temperature is preferably 50 to 200°C, more preferably 70 to 180°C, and even more preferably 90 to 160°C, from the viewpoint of promoting the curing reaction of the isocyanate compound (C). In order to prevent thermal deterioration or thermal decomposition of the polymer (B), it is preferable to remove the solvent (D) at a temperature lower than the melting point (Tm) of the polymer (B). The amount of the solvent (D) remaining in the layer (II) after drying is preferably 0.5% by mass or less, more preferably 0.05% by mass or less, and even more preferably 0.01% by mass or less.
[0086] <Applications of laminates> The laminate of the present disclosure has excellent releasability as described above, and therefore can be suitably used as a release film. Examples of the release film include a release film used in the manufacturing process of optical components, a release film used in the manufacturing process of thin-film ceramic capacitors, a separator for tapes and other adhesives, a separator for adhesives and resin sheet film formation, or a separator for architectural window films. Examples of optical components include a light guide plate, a polarizing film, a light diffusion film, a retardation film, and an anti-reflection film.
[0087] Since the laminate of the present disclosure has excellent heat resistance as described above, it can be suitably used as a protective film for, for example, a display device, a semiconductor device, an optical member, a printed circuit board, a capacitor, etc. EXAMPLES
[0088] The laminate of the present disclosure will be described more specifically below based on examples, but the laminate of the present disclosure is not limited to these examples in any way.
[0089] <Method of measuring physical properties of polymer> [composition] The content of the structural unit (U1) derived from 4-methyl-1-pentene in the 4-methyl-1-pentene polymer (A) and the content of the structural unit (U2) derived from an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) are obtained using the following apparatus under the following conditions. 13 It was calculated from C-NMR spectrum. Hereinafter, the content of the structural unit (U1) is also referred to as 4-methyl-1-pentene amount, the α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) is also referred to as comonomer type, and the content of the structural unit (U2) is also referred to as comonomer amount.
[0090] A nuclear magnetic resonance spectrometer, ECP500, manufactured by JEOL Ltd., was used. Solvent: o-dichlorobenzene / heavy benzene (80% by volume / 20% by volume) mixed solvent. Sample concentration: 55 mg / 0.6 mL. Measurement temperature: 120°C. Observation nuclei:13 The measurements were performed under the following conditions: C (125 MHz), sequence: single pulse proton decoupling, pulse width: 4.7 μsec (45° pulse), repetition time: 5.5 sec, number of integrations: 10,000 or more, chemical shift reference value: 27.50 ppm. 13 The compositions of 4-methyl-1-pentene and α-olefins were quantified by C-NMR spectroscopy.
[0091] [Intrinsic viscosity [η]] The intrinsic viscosity [η] was measured at 135° C. using decalin as a solvent. That is, about 20 mg of the sample polymer (A) or polymer (B) was weighed out, dissolved in 15 mL of decalin, and the specific viscosity η sp The decalin solution was diluted with 5 mL of decalin solvent, and the specific viscosity η was measured in the same manner. sp This dilution procedure was repeated two more times, and the η sp The value of / C was calculated as the intrinsic viscosity (see the formula below). [η]=lim(η sp / C) (C→0)
[0092] [Graft modification amount] The graft modification amount of the graft-modified 4-methyl-1-pentene polymer (B), i.e., the content of the structural units derived from the ethylenically unsaturated monomer used for the graft modification when the mass of the graft-modified 4-methyl-1-pentene polymer (B) is taken as 100 mass%, was determined by the following method.
[0093] First, the sample graft-modified 4-methyl-1-pentene polymer (B) was treated at 250°C with 5 minutes of preheating and 3 minutes of pressing to prepare a pressed film, and the pressed film was subjected to IR measurement by a transmission method using a Fourier transform infrared spectrophotometer (FT-IR410, manufactured by JASCO Corporation). In the following production example, maleic anhydride was used for graft modification, so that the peak at 1860 cm -1 and 4321 cm -1 The amount of graft modification was calculated from the peak intensity.
[0094] [Melting point (Tm), endothermic end temperature (TmE), exothermic onset temperature (TcS) and crystallization temperature (Tc)] Using a differential scanning calorimeter (DSC) measuring device (model: DSC220C) manufactured by Seiko Instruments Inc., an exothermic-endothermic curve was obtained in accordance with ASTM D3418, and the melting point (Tm) and crystallization temperature (Tc) were determined as follows.
[0095] Approximately 5 mg of the sample was placed in a measurement aluminum pan, heated from 20°C to 280°C at a heating rate of 10°C / min, held at 280°C for 5 minutes, and then cooled to 20°C at a cooling rate of 10°C / min to obtain a crystallization (exothermic) curve. After holding at 20°C for 5 minutes, the temperature was again raised from 20°C to 280°C at a heating rate of 10°C / min to obtain a melting (endothermic) curve. The temperature at the apex of the crystallization peak that appeared during the first cooling was taken as the crystallization temperature (Tc). When multiple crystallization peaks were detected, the one with the highest temperature was taken as the crystallization temperature (Tc). The temperature at the apex of the melting peak that appeared during the second heating was taken as the melting point (Tm). When multiple melting peaks were detected, the one with the highest temperature was taken as the melting point (Tm).
[0096] The temperature at which endotherm ends in the melting (endothermic) curve is designated as the endothermic temperature (TmE). The temperature at which heat generation starts in the crystallization (exothermic) curve is designated as the startothermic temperature (TcS). The endothermic point is the point at which, in the melting (endothermic) curve near the end of endotherm, it can be confirmed that the curve deviates from the baseline on the high temperature side of the melting peak, and a difference in the amount of heat begins to appear. The start of exothermic heat is the point at which, in the crystallization (exothermic) curve near the start of exothermic heat, it can be confirmed that the curve deviates from the baseline on the high temperature side of the crystallization peak, and a difference in the amount of heat begins to appear.
[0097] <Preparation Example 1: Preparation of (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride> Using the method described in Preliminary Experiment 5 (paragraphs
[0346] to
[0348] ) of WO 2014 / 123212, (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride was synthesized.
[0098] <Production Example 1a: Production of Polymer (1a)> [Synthesis Example 1-1: Production of olefin polymerization catalyst] In a 200mL three-neck flask equipped with a stirrer and thoroughly purged with nitrogen, 30mL of purified decane and 14.65mmol of particulate solid polymethylaluminoxane with a D50 of 28μm and an aluminum atom content of 43% by mass (synthesized using the method described in International Publication No. 2014 / 123212) were charged under nitrogen flow at 30℃ to obtain a suspension. 50.0mg (0.0586mmol) of (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride obtained in Preparation Example 1 was added to the suspension as a 4.58mmol / L toluene solution while stirring. After 1 hour, the stirring was stopped, and the resulting mixture was washed with 100 mL of decane by decantation, and then decane was added to obtain 50 mL of a slurry liquid (zirconium atom carrying rate 98%).
[0099] [Synthesis Example 1-2: Preparation of prepolymerization catalyst component] The slurry liquid prepared in Synthesis Example 1-1 was charged into a reactor equipped with a stirrer and thoroughly purged with nitrogen. 1.0 mL of a decane solution of triisobutylaluminum (TIBAL) (0.5 mmol / mL in terms of aluminum atom) was added to the above slurry liquid under nitrogen flow at 25°C. After cooling to 15°C, 10 mL of 4-methyl-1-pentene was charged into the reactor over 60 minutes. The start of the charging of 4-methyl-1-pentene was regarded as the start of prepolymerization. Stirring was stopped 2 hours after the start of prepolymerization, and the resulting mixture was washed three times with 100 mL of decane by decantation. The prepolymerization catalyst component was a decane slurry (9.5 g / L, 0.56 mmol / L in terms of zirconium atom).
[0100] [Preparation of polymer (1a)] At room temperature and under a nitrogen stream, 425 mL of purified decane was charged into a SUS polymerization vessel equipped with a stirrer having an internal volume of 1 L, and the temperature was raised to 40°C. After reaching 40°C, 0.8 mL (0.4 mmol in terms of aluminum atoms) of a decane solution of triisobutylaluminum (TIBAL) (0.5 mmol / mL in terms of aluminum atoms) was charged, and then 0.00175 mmol in terms of zirconium atoms of a decane slurry of the prepolymerization catalyst component of Synthesis Example 1-2 was charged. 23.75 NmL of hydrogen was charged, and then a mixture of 230 mL of 4-methyl-1-pentene and 22.4 mL of Linearene 168 (product name: Idemitsu Kosan Co., Ltd., a mixture of 1-hexadecene and 1-octadecene) was continuously charged into the polymerization vessel at a constant rate over 2 hours. The start of charging the above mixture was regarded as the start of polymerization, and the temperature was maintained at 45°C for 4.5 hours. 23.75 NmL of hydrogen was charged 1 hour and 2 hours after the start of polymerization. 4.5 hours after the start of polymerization, the temperature was lowered to room temperature, the pressure was released, and the polymerization liquid containing a white solid was immediately filtered to obtain a solid substance. This solid substance was dried at 80°C under reduced pressure for 8 hours to obtain polymer (1a). The yield was 142 g. The content of structural unit (U1) in polymer (1a) was 96.5 mol%, and the content of structural unit (U2) was 3.5 mol%. The melting point (Tm) of polymer (1a) was 201°C, and the intrinsic viscosity [η] (in decalin at 135°C) was 1.0 dl / g. Other physical properties of polymer (1a) are shown in Table 1.
[0101] <Production Example 1b: Production of polymer (1b)> 100 parts by mass of polymer (1a), 2 parts by mass of maleic anhydride, and 0.02 parts by mass of 2,5-dimethyl-2,5-bis(t-butylperoxy)hexyne-3 (Perhexyne 25B, manufactured by NOF Corporation) as an organic peroxide were blended and kneaded using a Labo Plastomill mixer manufactured by Toyo Seiki Seisakusho Co., Ltd. at a resin temperature of 280°C and a screw rotation speed of 150 rpm to obtain polymer (1b).
[0102] The content of the structural unit (U1) and the structural unit (U2) in the polymer (1b) was the same as that in the polymer (1a). The melting point (Tm) of the polymer (1b) was 201°C, the intrinsic viscosity [η] (in decalin at 135°C) was 1.0 dl / g, and the amount of graft modification was 1.5 mass%. Other physical properties of the polymer (1b) are shown in Table 1.
[0103] <Production Examples 2 to 7: Production of Polymers (2b) to (7b)> Polymers (2b) to (7b) were obtained in the same manner as in Production Examples 1a and 1b, except that the production conditions were changed so that the amount of 4-methyl-1-pentene, the type of comonomer, the amount of comonomer, and the amount of graft modification were as shown in Table 1. Various physical properties of polymers (2b) to (7b) are shown in Table 1.
[0104] <Production Example 8: Production of polymer (8a)> 500 mL of 4-methyl-1-pentene and 220 mL of heptane were charged at 23°C into a 1.5 L stainless steel autoclave equipped with an agitator, which had been thoroughly purged with nitrogen. 30 mL of 1-decene and 0.3 mL of a 1.0 mmol / mL toluene solution of triisobutylaluminum (TIBAL) were then charged into the autoclave, and stirring was started. Next, 140 mL of hydrogen was charged into the autoclave, and the autoclave was heated to an internal temperature of 60°C.
[0105] Thereafter, 2 mL of a toluene solution containing 0.039 mmol of previously prepared liquid methylaluminoxane in terms of aluminum atom and 0.00013 mmol of the (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride obtained in Preparation Example 1 was pressurized into the autoclave with nitrogen to initiate polymerization.
[0106] During the polymerization reaction, the temperature inside the autoclave was adjusted to 60°C. 10 minutes after the start of polymerization, 5 mL of methanol was injected into the autoclave with nitrogen to terminate the polymerization, and the autoclave was depressurized to atmospheric pressure. The reaction solution was poured into acetone with stirring to precipitate the polymer. The obtained polymer (8a) was dried at 130°C under reduced pressure for 10 hours. Various physical properties of the polymer (8a) are shown in Table 1.
[0107] <Production Example 9: Production of polymer (9a)> 500 mL of 4-methyl-1-pentene and 230 mL of heptane were charged at 23°C into a 1.5 L stainless steel autoclave equipped with an agitator, which had been thoroughly purged with nitrogen. 15 mL of 1-decene and 0.3 mL of a 1.0 mmol / mL toluene solution of triisobutylaluminum (TIBAL) were then charged into the autoclave, and stirring was started. Next, 140 mL of hydrogen was charged into the autoclave, and the autoclave was heated to an internal temperature of 60°C.
[0108] Thereafter, 2 mL of a toluene solution containing 0.06 mmol of previously prepared liquid methylaluminoxane in terms of aluminum atom and 0.0002 mmol of the (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride obtained in Preparation Example 1 was pressurized into the autoclave with nitrogen to initiate polymerization.
[0109] During the polymerization reaction, the temperature inside the autoclave was adjusted to 60°C. 30 minutes after the start of polymerization, 5 mL of methanol was injected into the autoclave with nitrogen to terminate the polymerization, and the autoclave was depressurized to atmospheric pressure. The reaction solution was poured into acetone with stirring to precipitate the polymer. The obtained polymer (9a) was dried at 130°C under reduced pressure for 10 hours. Various physical properties of the polymer (9a) are shown in Table 1.
[0110] [Table 1]
[0111] <Preparation of composition (X)> [Preparation of compositions (Xc1) and (X1-1)] To 100 parts by mass of polymer (1b), 0.1 parts by mass of tri(2,4-di-t-butylphenyl)phosphate as an antioxidant and 0.1 parts by mass of n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate as a heat stabilizer were added, and methylcyclohexane (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was added so that the solid content concentration was 6.25% by mass, and the mixture was stirred at 90°C for 3 hours at 200 rpm. Thereafter, ethyl acetate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was added so that the solid content concentration was 5% by mass, and the mixture was stirred at 60°C for 15 minutes at 200 rpm to prepare a composition (Xc1) containing polymer (1b).
[0112] After the temperature of the composition (Xc1) was lowered to 23°C, 0.6 parts by mass of Takenate D170N (manufactured by Mitsui Chemicals, Inc.) was added as the isocyanate compound (C) to 100 parts by mass of the polymer (1b) in the composition (Xc1), and the mixture was stirred at 200 rpm for 5 minutes. In this way, a composition (X1-1) containing the polymer (1b) and the isocyanate compound (C) was prepared as a coating agent.
[0113] [Preparation of compositions (X1-2) to (X1-4)] Compositions (X1-2) to (X1-4) were prepared as coating agents in the same manner as in the preparation of composition (X1-1), except that the amount of isocyanate (C) was changed as shown in Table 2.
[0114] [Preparation of compositions (X2) to (X7)] Compositions (X2) to (X7) were prepared as coating agents in the same manner as in the preparation of composition (X1-2), except that the polymer type was changed as shown in Table 2.
[0115] [Preparation of compositions (Xc8-1) and (Xc8-2)] To 100 parts by mass of polymer (8a), 0.1 parts by mass of tri(2,4-di-t-butylphenyl)phosphate as an antioxidant and 0.1 parts by mass of n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate as a heat stabilizer were added, and methylcyclohexane (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was added so that the solid concentration became 5% by mass. The mixture was stirred at 200 rpm at 90°C for 1 hour to prepare a composition (Xc8-1) containing polymer (8a).
[0116] After the temperature of the composition (Xc8-1) was lowered to 23°C, 0.8 parts by mass of Takenate D170N (manufactured by Mitsui Chemicals, Inc.) was added as the isocyanate compound (C) to 100 parts by mass of the polymer (8a) in the composition (Xc8-1), and the mixture was stirred at 200 rpm for 5 minutes. In this way, a composition (Xc8-2) containing the polymer (8a) and the isocyanate compound (C) was prepared as a coating agent.
[0117] [Preparation of compositions (Xc9) to (Xc10)] A coating agent was prepared in the same manner as in the preparation of composition (Xc8-2), except that the polymer type was changed as shown in Table 2.
[0118] [Example 1] Polypropylene (Prime Polymer Co., Ltd., brand: Prime Polypro F113G, melting point (Tm): 163°C, MFR: 3.0g / 10min) was molded into a film using a T-die cast film molding machine at a cylinder temperature of 230°C to obtain a cast film (substrate film (I-1)) having a thickness of 100 μm. The substrate film (I-1) was subjected to a corona treatment to obtain a substrate film (I-2). The obtained substrate film (I-2) was used as the substrate layer (I).
[0119] The settings of the applicator were adjusted so that the layer (II) formed from the composition (X1-1) prepared above had a thickness of 0.3 μm after drying, and the composition (X1-1) was applied to the corona-treated surface of the substrate film (I-2) prepared above at 25° C., uniformly spread with the applicator, and then dried at 100° C. for 20 seconds to form a layer (II). In this way, a laminate including the substrate film (I-2) and the layer (II) was obtained. The physical properties of the resulting laminate were evaluated, and the results are shown in Table 2.
[0120] [Examples 2 to 12, Comparative Examples 1 to 5] A laminate was produced and its physical properties were evaluated in the same manner as in Example 1, except that each element was changed as shown in Table 2. The obtained results are shown in Table 2.
[0121] [Comparative Example 6] The substrate film (1-I) was used as it was to measure the water contact angle and surface free energy. The results are shown in Table 2.
[0122] [Storage stability] When preparing compositions (X) and (Xc) as coating agents, the isocyanate compound (C) (Takenate D170N) was added, and the coating agent was stored at room temperature (23°C) for 24 hours. The liquid viscosity of the coating agent immediately after the addition of the isocyanate compound (C) and 24 hours after the addition was measured using a B-type viscometer at room temperature (23°C) to evaluate storage stability. For compositions without the isocyanate compound (C), the liquid viscosity of the coating agent immediately after the preparation of the composition and 24 hours after the preparation was measured using a B-type viscometer at room temperature (23°C) to evaluate storage stability. (Evaluation Criteria) Δ(liquid viscosity) = liquid viscosity 24 hours after addition - liquid viscosity immediately after addition A:Δ(liquid viscosity)<100000 B:Δ(liquid viscosity)≧100000
[0123] [Surface free energy] Distilled water, diiodomethane and bromonaphthalene were selected as liquids with different surface tensions, and the surface free energy was determined using these liquids. Specifically, the selected liquid was dropped onto the surface of layer (II) or layer (IIc) of the laminate prepared above, and the wetting state of the laminate by the liquid was analyzed using a DropMaster500 image processing type solid-liquid interface analysis system (manufactured by Kyowa Interface Science Co., Ltd.) to determine the surface free energy (mN / m) of layer (II) or layer (IIc). In the case of Comparative Example 6, the surface free energy of the substrate film was determined. (Evaluation method) Test temperature and humidity: 23℃, 50%RH Dripping amount: 1.5μL Measurement time: 10 seconds after dropping Extended Fowkes theory
[0124] [Water contact angle measurement] A contact angle value was measured when a water droplet was dropped on the surface of layer (II) or layer (IIc) of the laminate obtained in the Examples and Comparative Examples using a DropMaster500 image processing type solid-liquid interface analysis system (manufactured by Kyowa Interface Science Co., Ltd.) In the case of Comparative Example 6, the contact angle value of the substrate film was measured. (Evaluation method) Test temperature and humidity: 23℃, 50%RH Dripping amount: 1.5μL Measurement time: 10 seconds after dropping
[0125] [Evaluation of adhesion between substrate layer (I) and layer (II) or layer (IIc)] A lattice pattern was applied to the surface of the layer (II) or layer (IIc) of the obtained laminate according to the cross-cut method described in JIS K5600-5-6:1999 to prepare a test piece. However, the number of lattices was changed to 100, and the test piece was evaluated as follows. After an adhesive tape (manufactured by Nichiban Co., Ltd., Cellotape (registered trademark)) was applied to the lattice pattern of the test piece, the tape was quickly pulled in a 60 degree direction to peel it off, and the number of lattices that were not peeled off out of the 100 lattices was counted to evaluate the adhesion between the base layer (I) and the layer (II) or layer (IIc). (Evaluation Criteria) A: The number of lattices that were not peeled off was 100. B: The number of lattices that were not peeled off is 99 or less.
[0126] [Table 2]
[0127] [Table 3]
[0128] [Table 4] [Explanation of symbols]
[0129] 1: Laminate 10: Substrate layer (I) 20, 20A, 20B: Layer (II)
Claims
1. A substrate layer (I); A layer (II) formed of a composition (X) containing a graft-modified 4-methyl-1-pentene polymer (B) and an isocyanate compound (C) that satisfy the following requirements (a) to (c); A laminate comprising: (a) a melting point (Tm) measured by differential scanning calorimetry (DSC) of more than 180°C and not more than 220°C; (b) the endothermic end temperature (TmE) in the melting (endothermic) curve measured by differential scanning calorimetry (DSC) is 230° C. or lower; (c) The heat generation onset temperature (TcS) in the crystallization (heat generation) curve measured by a differential scanning calorimeter (DSC) is 210° C. or lower.
2. 2. The laminate according to claim 1, wherein the graft-modified 4-methyl-1-pentene polymer (B) has an intrinsic viscosity [η] of 0.5 to 5.0 dl / g as measured in decalin at 135° C.
3. the graft-modified 4-methyl-1-pentene polymer (B) is a graft-modified product of the 4-methyl-1-pentene polymer (A), The 4-methyl-1-pentene polymer (A) comprises a structural unit (U1) derived from 4-methyl-1-pentene, and, if desired, a structural unit (U2) derived from an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene), In the 4-methyl-1-pentene polymer (A), the content of the structural unit (U1) is 84 to 100 mol %, and the content of the structural unit (U2) is 0 to 16 mol % (the total of the content of the structural unit (U1) and the content of the structural unit (U2) is 100 mol %). The laminate according to claim 1 .
4. The laminate according to claim 1 , wherein the substrate layer (I) comprises a polyolefin having a melting point (Tm) of 200° C. or less as measured by a differential scanning calorimeter (DSC).
5. 2. The laminate according to claim 1, wherein the graft-modified amount of the graft-modified 4-methyl-1-pentene polymer (B) is 0.1 to 5.0% by mass.
6. The laminate according to claim 1, wherein in the composition (X), a content of the isocyanate compound (C) is 0.2 to 30 parts by mass per 100 parts by mass of the graft-modified 4-methyl-1-pentene polymer (B).
7. 2. The laminate according to claim 1, wherein the surface free energy of the layer (II) on a surface opposite to the surface facing the base layer (I) is 32 mN / m or less.
8. 2. The laminate according to claim 1, wherein the layer (II) has a water contact angle of 97° or more on a surface opposite to the surface facing the base layer (I).
9. The laminate according to claim 3, wherein the structural unit (U2) of the 4-methyl-1-pentene polymer (A) is a structural unit derived from an α-olefin having 6 to 18 carbon atoms (excluding 4-methyl-1-pentene).
10. The laminate according to claim 1 or 2, wherein the thickness of the layer (II) is 25 μm or less.
11. The laminate according to claim 4, wherein the polyolefin having a melting point (Tm) of 200° C. or less in the base layer (I) includes at least one selected from the group consisting of polypropylene and polyethylene.
12. The laminate according to claim 11, wherein the polyolefin having a melting point (Tm) of 200° C. or less in the base layer (I) comprises polypropylene.
Citation Information
Patent Citations
Composition, film and method for producing the film
JP2013227421A
Composition, film, and method for producing the film
JP2015034258A
Laminate and release paper
JP2017074775A